2023
DOI: 10.1021/acschembio.3c00063
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Guided Discovery of the Myxobacterial Thiolactone-Containing Sorangibactins

Abstract: In this study, an unprecedented myxobacterial siderophore termed sorangibactin was discovered by heterologous expression of a coelibactin-like nonribosomal peptide synthetase (NRPS) gene cluster from the Sorangiineae strain MSr11367 in the host Myxococcus xanthus DK1622. De novo structure elucidation uncovered a linear polycyclic structure consisting of an N-terminal phenol group, an oxazole, tandem N-methyl-thiazolidines, and an unusual C-terminal γ-thiolactone moiety. Except for the unprecedented oxazoline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…It is remarkable that a concomitant study reported some of these chelators as metabolites ("sorangibactins") of selected myxobacteria. [26] In contrast to other salicylatederived metallophores, the anthrochelins and sorangibactins have two uncommon features: an oxazole ring and an unusual homocysteine moiety. The presence of this homocysteine tag, which might also occur in the form of a thiolactone, is highly unusual and unexpected, as the peptide structure is not colinear with the assembly line, that is, there is no module for the incorporation for this terminal amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…It is remarkable that a concomitant study reported some of these chelators as metabolites ("sorangibactins") of selected myxobacteria. [26] In contrast to other salicylatederived metallophores, the anthrochelins and sorangibactins have two uncommon features: an oxazole ring and an unusual homocysteine moiety. The presence of this homocysteine tag, which might also occur in the form of a thiolactone, is highly unusual and unexpected, as the peptide structure is not colinear with the assembly line, that is, there is no module for the incorporation for this terminal amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…The hCys residue in sorangibactins is cyclized to form γthiolactone. [57] The biological activity of argyrins and tubulysins were thoroughly evaluated. Argyrins showed potent immunosuppressive activity by selectively inhibiting the human immunoproteasome β1i, [60] narrow spectrum antibacterial activity due to the inhibition of protein synthesis by binding in a unique site of the elongation factor G, [60a,61] and antitumor activity by stabilizing the cyclin kinase inhibitor p27 kip1 through proteasome inhibition.…”
Section: Figurementioning
confidence: 99%
“…[58a,b] The other biological activity observed within these NPs was sorangibactins' siderophore-like activity. [57] Sorangibactins and chloromyxamides did not display antimicrobial or anticancer activity, [56][57] and vioprolides were not evaluated for biological activities.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations